To the issue of strength assessment of the pipeline-composite bandage system - L.S. Shlapak, L. S.; Maksymuk, O. V.; Shyrokov, V. V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2017)
acteristics of material there originate residual stresses and strains that can lead to the loss of its bearing capacity in pipes. One of the ways to increase the structural strength of pipelines is to strengthen the pipe by banding, which results in the need to develop methods for calculating the structural parameters of the pipeline – bandage system. This paper presents a mathematical model to estimate the strength of the pipeline-composite bandage system, based on the improved theory of thin shells with regard to shear and compression pliability of material. The solution allows us to simulate the stress state of a finite-length pipeline based on the given original characteristics of the pipes` material, composite, operational loads and effects.